Serum Cytokines Th1, Th2, and Th17 Expression Profiling in Active Lupus Nephritis-IV: From a Southern Chinese Han Population - Keshav Raj Sigdel; Lihua Duan; Yin Wang; Weiping Hu; Ning Wang; Qingyi Sun; Qingyan Liu; Xiaocong Liu; Xianghua Hou; Ao Cheng; Guixiu Shi; Yanlin Zhang (Mediators of Inflammation)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by aberrant T cell immune response. Diffuse proliferative lupus nephritis (LN-IV) is the most common, severe, and active form of lupus nephritis. In this study, we investigated the production of Th1, Th2, and Th17 cytokines in prediction of active form of LN-IV. ProcartaPlex multiplex immunoassays panels were used for detection of serum Th1, Th2, and Th17 cytokines profiling. Th1 and Th17 cytokines (IL-18, IFN-γ, IL-12p70, IL-6, and IL-17A) were considerably expressed in the serum of lupus nephritis IV patients in comparison to the healthy control. However, only IL18 and IL6 were higher in class IV versus class III lupus nephritis. Importantly, the ratios of Th1/Th2 (IL-18/IL-4) and Th17/Th2 (IL-17A/IL-4) were significantly elevated in LN-IV when compared with LN-III, LN-V, and healthy controls. Consistently, the serum cytokines IL-18, IL-17A, and IFN-γ were markedly expressed in LN-IV patient glomeruli and interstitial tissue compared to other classes of LN by IHC. ROC further suggests that IL-18 was a potential marker for LN-IV. The data from our study suggests that the early detection and quantification of these cytokines may help in prediction of active form of LN-IV.